Sustainable Tourism in Jatiluwih Village: Analysis of Green Accounting Implementation in Tourism Destination Operations - LESTARI, Nyoman Sophia Andriani; VIRANTI, Aulia; SRINU, Srinu; PRAMITA, Silvi (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This study aims to explore and analyze the implementation of Green Accounting in the operation of Jatiluwih Village tourist destination as one of the sustainable tourist destinations in Bali. Jatiluwih Village is known for its beautiful green terraced rice fields which are a cultural heritage. The main objective of this study is to determine the extent to which accounting, in its role, provides a positive impact on the management of a sustainable tourist destination.Methodology:The methods used in data collection are literature studies, literature analysis, and direct observation in the field. The results of the study indicate that Jatiluwih Tourism Village has indirectly implemented Green Accounting through its sustainable agricultural practices, which is in line with the principles of Green Accounting.Findings:Although not all village management discusses Green Accounting as a whole, the implementation of Subak itself plays an important role as a tool to support sustainable tourism development in Jatiluwih Village and increase awareness and transparency in natural resource management so as to encourage efficient use and more responsible decision-making.Implication:This research is expected to provide a general overview of the importance of implementing accounting, especially Green Accounting, in the sustainable tourism sector.